PENGARUH KONSEP DIRI TERHADAP KOMUNIKASI INTERPERSONAL MAHASISWA - Irawan, Sapto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
This study aimed to test the significance effect of self-concept on studentsâ interpersonal communication. Subjects in this reasearch were guidance and counseling students in Satwa Wacana Christian University, Salatiga. Analysis of data used simple regression to determine the effect of self-concept on studentsâ interpersonal communication. The results showed that Sig. = 0.012, which means that there was a significant relationship between self-concept and interpersonal communication. Besides, the value of R Square or determination coefficient was 0.048, which means that self-concept has the contribution effect of a 4.8% on the student interpersonal communication, while the remaining 95.2% was influenced by other factors. It can be concluded that there is a significant relationship between self-concept on studentsâ interpersonal communication.